POU2F2‐IL‐31 Autoregulatory Circuit Converts Hepatocytes into the Origin Cells of Hepatocellular Carcinoma. Issue 13 (2nd May 2021) - Yuan, Chunwang; Pang, Lijun; Wang, Wenjing; Ouyang, Yabo; Guo, Xianghua; Liu, Kai
Abstract: Hepatocellular carcinoma (HCC) originates from fully differentiated hepatocytes, but the decisive events for converting hepatocytes to the cells of origin for HCC are still unclear. Liver cancer stem cells (LCSCs) cause HCC but are not bona fide cells of origin. Here, the expressions of POU2F2 and IL‐31 are identified in macroscopically normal livers of diethylnitrosamine‐challenged mice. An autoregulatory circuit formed by mutual induction between POU2F2 and IL‐31 drives hepatocytes to progress to LCSCs by acquiring stemness, as well as stimulates them to in vivo grow and malignantly progress. The development of the autoregulatory circuit is a decisive event for converting hepatocytes into the cells of origin, since hepatocytes expressing the circuit have acquired tumorigenic potential before progressing to LCSCs. Nonetheless, acquiring stemness is still required for the cells of origin to initiate hepatocarcinogenesis. The circuit also occurs in human cirrhotic tissues, partially elucidating how premalignant lesions progress to HCC. Abstract : POU2F2 and IL‐31 form an autoregulatory circuit that functionally promotes fully differentiated hepatocytes to be converted into liver cancer stem cells by inducing pluripotent transcription factors such as NANOG, OCT4, and SOX2, as well as suppressing p53.